Understanding the spatial variation of sea level rise in the North Sea using satellite altimetry. Issue 8 (22nd August 2017) - Sterlini, Paul; Le Bars, Dewi; de Vries, Hylke; Ridder, Nina
Abstract: This paper examines the spatial variation of sea surface height trends in the North Sea Basin as seen by satellite altimetry and assesses its underlying causes. Changes in the potential temperature and salinity of the North Sea are transposed into corresponding changes in sea surface height and regional anomalies of linear sea level trend calculated. The same is carried out for the meteorological processes which act on the sea surface. The steric and meteorological regional sea level rise anomalies are summed with those from contributions from land ice and compared against the values seen by satellite altimetry over the period 1993–2014. Results show that there is good agreement between the observations and the reconstruction. The local meteorological contribution appears to be most important in describing regional variation in linear sea level rise and is reinforced with a local halosteric contribution which shows a similar spatial pattern. Key Points: Meteorological effects account for most of the observed regional variation in linear SLR in the North Sea Basin Local halosteric processes and, to a lesser extent, nonlocal thermosteric processes also describe the observed variation in linear SLR